2003
DOI: 10.1364/ol.28.002058
|View full text |Cite
|
Sign up to set email alerts
|

Laser terahertz-emission microscope for inspecting electrical faults in integrated circuits

Abstract: A laser terahertz-emission microscope (LTEM) system is proposed and developed for inspecting electrical faults in integrated circuits (IC). We test a commercial operational amplifier while the system is operating. Two-dimensional terahertz-emission images of the IC chip are clearly observed while the chip is scanned with a femtosecond laser. When one of the interconnection lines is cut, the damaged chip has a LTEM image different from that of normal chips. The results indicate that the LTEM system is a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(70 citation statements)
references
References 12 publications
0
70
0
Order By: Relevance
“…Following earlier work on integrated circuits [114], Yamashita et al demonstrated in 2008 the used of THz to detect electrical failures in semiconductors. To do so, they found out that p-n junctions can be excited by ultrafast laser pulses and, therefore, generate photocurrents which propagate along the different interconnections and produce THz pulses.…”
Section: Electrical Failures In Semiconductorsmentioning
confidence: 98%
“…Following earlier work on integrated circuits [114], Yamashita et al demonstrated in 2008 the used of THz to detect electrical failures in semiconductors. To do so, they found out that p-n junctions can be excited by ultrafast laser pulses and, therefore, generate photocurrents which propagate along the different interconnections and produce THz pulses.…”
Section: Electrical Failures In Semiconductorsmentioning
confidence: 98%
“…148 LTEM has been also used for inspection of semiconductor devices. [149][150][151] Sakai et al 152 have demonstrated laser-induced THz emission from the surface of GaN, which can be used for determination of the defect density and surface potential. They observed that when the GaN surface is excited by ultraviolet femtosecond laser pulses, the THz emission is enhanced by defects related to yellow luminescence (YL).…”
Section: Laser-induced Thz Emission Spectroscopy For Visualization Ofmentioning
confidence: 99%
“…We also notice the use of high power sources [77], CW gas laser [78], coherent or incoherent detectors and any combination of all these devices [79]. Moreover, a lot of new techniques have emerged such as polarization imaging [80] dark-field imaging [81], single-pixel imaging [82][83][84] and compressive imaging technique [85], real time imaging [86], time reversal imaging [87], terahertz microscope [88,89] and interferometric imaging [90,91]. This is just to mention that terahertz imaging has given rise to a lot of attention and developments during this last decade.…”
Section: Time Domain Techniquesmentioning
confidence: 99%